Growing and stabilizing metallic nanoparticles inside mesoporous oxide thin films - Zalduendo, María Mercedes (2022)
Metallic nanoparticles (NPs) have interesting size-dependent optical properties and a high surface to volume ratio that make them appealing for many different applications, such as sensing, catalysis, energy conversion and storage, biomedicine, etc. These applications require avoiding NPs degradation, coarsening and/or aggregation. The use of porous templates has become a promising strategy to attain this objective. In particular, ordered mesoporous oxides prepared by sol-gel reactions combined with supramolecular templates are highly appealing supports, due to their high specific surface and regular and accessible porosity. Moreover, if these oxides are prepared as thin films, the manipulation and integration in portable devices is straightforward.In this work, different alternatives to obtain metallic NPs stabilized within mesoporous oxide thin films are discussed. Firstly, the major effect of mesoporous TiO2 thin films pores ordering over the amount and distribution of Au NPs obtained within is presented, along with the discussion of the architecture effect over the materials sensing capabilities.Afterwards, the use of hybrid mesoporous thin films containing carboxylic and phosphonate groups as templates to form and stabilize Cu and Ag nanoparticles is presented. In all cases, the key effect of the surface chemistry over synthesis of the composites and their applications is highlighted.